Cuidar al cuidador: la ayuda psicoterapeútica a cuidadores de mayores dependientes mediante dinámica de grupos - Gil Escudero, Guillermo (Miscelánea Comillas, 2008)
Main family carers dedication, commitment, compassion and courage, allow elders dependents to remain in its family environment. Nevertheless, in many cases, the continuance at home is reached at the expense of a significant physical weakening and a notorious psychological debilitation of the main carer. In many occasions, the main carer task is a daily and continuous job that requires full time dedication. As a consequence, many carers of elder family members suffer an important physical and psychological overload. Group dynamics for carers of older people tries to repair the psychological damage caused by the stress producing factors of its life as carers and to re-establish a better adaptation to the caring situation. To achieve this, the group dynamics generates a facilitating environment for the psychological and emotional ventilation and relief. Also, the group creates a safe and trusting environment that facilitates analysis and awareness of carers situation and responses to the task and load of caring.